Poly C Binding Protein 1 Regulates p62/SQSTM1 mRNA Stability and Autophagic Degradation to Repress Tumor Progression - Zhang, Wenliang; Zhang, Shaoyang; Guan, Wen; Huang, Zhicong; Kong, Jianqiu; Huang, Chunlong; Wang, Haihe; Yang, Shulan (Frontiers in Genetics, 2020)
Accumulating evidence show that Poly C Binding Protein 1 (PCBP1) is deleted in distinct types of tumors as a novel tumor suppressor, but its tumor suppression mechanism remains elusive. Here, we firstly describe that downregulation of PCBP1 is significantly associated with clinical ovarian tumor progression. Mechanistically, PCBP1 overexpression affects various autophagy-related genes expression at various expression levels to attenuate the intrinsic cell autophagy, including the autophagy-initiating ULK, ATG12, ATG7 as well as the bona fide marker of autophagosome, LC3B. Accordingly, knockdown of the endogenous PCBP1 in turn enhances autophagy and less cell death. Meanwhile, PCBP1 upregulates p62/SQSTM1 via inhibition p62/SQSTM1 autophagolysome and proteasome degradation as well as its mRNA stability, consequently accompanying with the caspase 3 or 8 activation for tumor cell apoptosis. Importantly, clinical ovary cancer sample analysis consistently validates the relevance of PCBP1 expression to both p62/SQSTM1 and caspase-8 to overall survival, and indicates PCBP1 may be a master player to repress tumor initiation. Taken together, our results uncover the tumorigenic mechanism of PCBP1 depletion and suggest that inhibition of tumor cell autophagy with autophagic inhibitors could be an effective therapeutical strategy for PCBP1-deficient tumor.